1695. Combination Therapy for the Investigational Polymyxin SPR206 and Meropenem (MEM) Increases the Rapidity and Extent of Killing of Pseudomonas aeruginosa (PA) and Prevents the Bacterium from Emerging Resistant to Both Antibiotics. (15th December 2022) - Louie, Arnold; Bader, Justin; Cotroneo, Nicole; Lister, Troy; Liu, Weiguo; Brown, David; Myrick, Jenny; Drusano, George
Abstract: Background: The CDC lists multidrug-resistant PA as a Serious Threat pathogen causing 32, 200 hospital infections and 2, 700 deaths in the US in 2017. PA resistance is frequent with antibiotic monotherapies. SPR206 is a next generation polymyxin that, in a first in human study, was generally safe and well tolerated at the potential therapeutic dose of 100 mg IV Q8h. The aim of this study was to quantify the dose-range PA killing activity of SPR206 monotherapy in a hollow fiber infection model (HFIM) and to assess if the combination of SPR206 and MEM more effectively reduces bacterial burden and prevents development of resistance than either drug alone. Methods: Agar dilution MICs and mutation frequencies (MFs) for SPR206, PMB, & MEM were performed for PA ATCC 27853. A 10-day HFIM dose range study simulating the free PK profiles for SPR206 (50 – 600 mg IV Q8h) quantified PA killing and possible regrowth. A HFIM study compared single vs combination SPR206 100 mg IV Q8h over 1h and MEM 2g IV Q8h over 1h regimens for enhanced PA killing and resistance suppression. Results: The SPR206, PMB, & MEM MICs were 0.5, 0.5, and 0.25 mg/L, respectively. The MFs for SPR206 and PMB to 3x, 5x and 8x MIC were -6.2, -6.9, & -7.7 log CFU and -5.3, -6.4, & -7.7 log CFU, respectively. The MF for 3x MIC of MEM was -6.8 log CFU. In a dose-range HFIM, simulated regimens for 50 – 600 mg IV Q8h showed a dose-response effect, with 2.9 – 7.3 log CFU/mL reductions in PA seen at 5h. All regimens had regrowth by isolates with SPR206 MICs of 1 – 8 mg/L. In a HFIM study simulating the SPR206 and MEM clinical regimens, alone and in combination, SPR206 alone killed 5 log CFU/mL of PA at 5h, followed by regrowth. MEM alone killed 3.5 log CFU/mL of PA at 5h, with maximum kill seen on Day 4, followed by regrowth. SPR206 plus MEM killed 0.8 log CFU/mL more PA at 5h vs SPR206 alone and had undetectable PA counts by day 4. Combination therapy prevented regrowth (see figure). Conclusion: Conclusions: SPR206 (100 mg IV Q8h) killed 5 log CFU/mL of PA at 5h, but regrowth ensued. SPR206 plus MEM produced 0.8 log CFU/mL more killing of PA at 5h. The killing activity of the 2-drug regimen combined with its resistance prevention effect resulted in undetectable PA counts by Day 4 of treatment. Disclosures: Arnold Louie, MD, Curza, Inc.: Grant/Research Support|Prokaryotics: Grant/Research Support|Spero Therapeutics: Grant/Research Support Nicole Cotroneo, B.S., Spero Therapeutics: Employee|Spero Therapeutics: Stocks/Bonds Weiguo Liu, M.D., Spero Therapeutics: Grant/Research Support David Brown, M.B.A., Curza, Inc.: Grant/Research Support|Prokaryotics: Grant/Research Support|Spero Therapeutics: Grant/Research Support Jenny Myrick, B.S., Spero Therapeutics: Grant/Research Support George Drusano, M.D., Curza: Advisor/Consultant|Curza: Grant/Research Support|Prokaryotics: Grant/Research Support|Spero Therapeutics: Grant/Research Support.